Effect of Capital Adequacy Ratio, Non Performing Loan and Loan to Deposit Ratio on Return On Assets in Banks listed on the Indonesia Stock Exchange for the 2015-2019 Period: Pengaruh Capital Adequacy Ratio, Non Performing Loan dan Loan to Deposit Ratio terhadap Return On Assets pada Perbankan yang terdaftar di Bursa Efek Indonesia Periode 2015-2019 - Fakhiroh, Silvi Zakiyatul; Hariasih, Misti (Indonesian Journal of Innovation Studies, 2021)
The technique of taking is using purposive sampling method. The sample in this study were 20 companies listed on the Indonesia Stock Exchange in 2015-2019.The data used in this study is secondary data taken from the Indonesia Stock Exchange. Data analysis uses Eviews 9 analysis with the aim of testing the capital adequacy ratio (X1), non performing loans (X2), loan to deposit ratio (X3), to return on assets (Y). The results of this study indicate that simultaneously there is a significant influence between the capital adequacy ratio, non-performing loans and loan to deposit ratios on return on assets. Meanwhile, partially non performing loans have a negative and significant effect on return on assets. The capital adequacy ratio has a negative and insignificant effect on return on assets.